An approach for the evaluation of herbaceous legumes with multiple benefits - Tarawali, Shirley A. (2000)
In order to promote the identification of herbaceous legumes that may contribute to weed control, soil fertility, crop production, and livestock enterprises, as a means of encouraging sustainable agricultural practices amongst resource-poor farmers, an evaluation method using a simple sampling approach is described. To illustrate the method, result from one experiment in the derived savanna of Nigeria conducted over a period of 2.5 years are presented. The experiment included 14 accessions of single legume species, 9 mixtures of species, and 4 grain-legume accessions (soybean and cowpea). Mixtures of species, including combinations of rapidly establishing and slowly establishing but more persistent species, were designed to stabilize yield and minimize the risk involved in introducing herbaceous legumes. Although the biomass production of the mixtures was less than the best single species, they did remain stable over the evaluation period. Whilst the rapidly establishing species disappeared from the mixtures after the establishment year, the other components were able to compensate for this, and mixtures had relatively stable yields throughout the period. Grain legumes produced substantial biomass only during the establishment year, but have the potential to contribute to systems where farmers' circumstances permit the use of inputs. Such variations, together with those relating to speed of establishment, biomass production, and persistence over the evaluation period, are discussed with respect to the need to identify species or mixtures that are suitable for farmers' socioeconomic circumstance as well as biophysical conditions.